Synthesis of Aza-polyquinanes via Fischer Indolization and Ring-Rearrangement Metathesis as Key Steps - Kotha, Sambasivarao; Keesari, Ramakrishna Reddy; Ansari, Saima (Synthesis, 2019)
Herein, we describe a simple synthetic strategy to assemble aza-polyquinane systems containing an indole motif by employing the Fischer indolization and ring-rearrangement metathesis as key steps. The precursor used here is exo-dicyclopentadienone, which is derived from less explored exo-dicyclopentadiene. By using this approach, several aza-polyquinanes that contain indole units and fused medium rings (eight- and nine-membered rings) were synthesized in good yields.
Keywords: exo-dicyclopentadiene; Fischer indolization; ring-rearrangement metathesis; aza-polyquinane; medium rings; polycyclic